Edible Film Application of Mung Bean Starch with the Addition Glycerol as a Button Mushrooms Packer - Firdausi, Karima Mumtaz; Sedyadi, Endaruji; Rahmayanti, Maya; Warsito, Gita Miranda (ALCHEMY:Journal of Chemistry, 2025)
The research on the production of edible films from mung bean starch with the addition of glycerol as packaging for button mushrooms aims to analyze the effect of varying glycerol concentrations on the physical and mechanical properties of the edible film, as well as the shelf life of button mushrooms in terms of weight loss. The stages of this research include the production of mung bean starch, the creation of edible films, characterization of the starch and edible films, and their application to button mushrooms using weight loss tests. The edible films were made with glycerol concentrations of 6.3%, 12.6%, and 18.9% of the total starch weight used. The results showed that the edible films at each glycerol variation exhibited a reduction in weight loss that was generally lower compared to the weight loss of the control button mushrooms.